Das System der Geschäftsstraßen und die innerstädtische Differenzierung in der orientalischen Stadt. (Fallstudie Teheran) - Seger, Martin (ERDKUNDE, 1979)
The socio-ecological differentiation of an oriental town is presented by an analysis of its business streets. Even the density of shops and the quality of their goods, i.e. the qualitative-quantitative criteria, can be interpreted as supply to extremely varied, differing social groups. At the same time phases of growth are shown, from the western-type city district with a recent CBD at the fore front of growth to the older business streets (from the time around 1930) which, having lost prestige and suffered social decline, form the rear of the system extending from the bazaar. As a new method to classify socio-ecologically different business streets and thus districts of the town branch associations are formed. They represent groups of business types, which, as a result of aiming at a certain group of customers (spatiallly concrete supply and demand system) are only to be found in certain limited parts of the town. Besides the socio-ecological principle of location of associations of shop types there is a central-peripheral gradient that reflects the inner-city centrality. It points to the co existence of two business street systems, the centres of which - bazaar and Western CBD - serve different social groups. Thus the bi-polarity of the westernized oriental city is established by way of the analysis of its business streets.